2002
DOI: 10.1051/lait:2002036
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of proteolysis during the ripening of traditional Feta cheese

Abstract: -Four cheesemaking trials were conducted in three different traditional Feta cheese plants. The characteristics of the cheesemaking process had to do with: the heat treatment of the cheese milk, the use of yoghourt as a starter, the use of traditional rennet from kids' and lambs' abomasa, and the packaging in wooden barrels without brine addition. At 60 d (minimum ripening period according to Greek Codex Alimentarius), the percentage of water soluble nitrogen (WSN) varied from 15.88% to 19.58% of total nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 14 publications
4
32
1
9
Order By: Relevance
“…In our study, the lack of notable degradation of caseins in rennet-free cheeses confirms this hypothesis. Similar observations were reported by Moatsou et al [33] for Feta cheese. Primary proteolysis of caseins in cheese is generally due mainly to the activity of chymosin (on α s1 -casein) and of plasmin (on β-casein) [17] but they are not the sole active proteolytic agents [29].…”
Section: Urea-pagesupporting
confidence: 92%
“…In our study, the lack of notable degradation of caseins in rennet-free cheeses confirms this hypothesis. Similar observations were reported by Moatsou et al [33] for Feta cheese. Primary proteolysis of caseins in cheese is generally due mainly to the activity of chymosin (on α s1 -casein) and of plasmin (on β-casein) [17] but they are not the sole active proteolytic agents [29].…”
Section: Urea-pagesupporting
confidence: 92%
“…The greatest part of the water-soluble nitrogen (>64 %) is consisted of nitrogen that is soluble in 12 % trichloroacetic acid (TCA), which corresponds to medium and small-sized (600-15.000 Dalton molecular mass) peptides with 2-22 amino acids (Moatsou et al, 2002;Roseiro et al, 2003). It was reported that rennet, bacterial proteinases and peptidases are responsible for the formation of some 12 % trichloroacetic acid-soluble nitrogen (TCA-SN) .…”
Section: Nitrogen Fractions In Tulum Cheesesmentioning
confidence: 99%
“…TCA-SN ratios of plastic cheeses were higher than skin cheeses followed by pot, cloth and stomach cheeses, respectively (Table 1) As proteolysis continues in cheese, relatively larger molecular weight nitrogenous fractions brought about by chymosin and cell-wall proteinases are further degraded to smaller molecular weight compounds by peptidases. The formation of amino acids and peptides with molecular weight less than 600 Dalton, which are soluble in 5 % phosphotungstic acid (PTA), is strongly related to the age and flavour intensity of cheese (Moatsou et al, 2002). The phosphotungstic acid-soluble nitrogen (PTA-SN) values, which occur as a result of peptidolysis are commonly used to determine the type and the extent of proteolysis (Moatsou et al, 2002;Roseiro et al, 2003).…”
Section: Nitrogen Fractions In Tulum Cheesesmentioning
confidence: 99%
See 1 more Smart Citation
“…В результаті катаболізму аміно-кислот утворюються такі леткі сполуки, як леткі жирні кислоти, альдегіди, спирти, сульфонільні компоненти, складні ефіри та інші сполуки [20][21][22]. Вільні аміно-кислоти та їх похідні є основними компонентами смако-ароматичної композиції сирів.…”
Section: результати дослідження та їх обговоренняunclassified